“Quem entrou quer ficar”: análise da assistência estudantil frente às demandas das mulheres estudantes com filhos da Universidade Federal do Maranhão - SOARES , Brenda Vanessa Pereira (2021)
The present dissertation entitled ""WHO WENT IN WANTS TO STAY": analysis of student assistance in the face of the demands of women students with children at the Federal University of Maranhão" aimed to analyze if, and in what way, the student assistance implemented by the University in question ( UFMA) has guaranteed the social right to education of students who are mothers in their undergraduate courses. The research was supported by the recognition of education as a fundamental human right that must be guaranteed by the State to all, as enshrined in the current Constitution. Women who are mothers face frequent challenges to reconcile motherhood and academic life, which points to the effectiveness of actions that provide them with this reconciliation, from their admission to the completion of higher education. The methodology used relied on the weaving between theory and empirical, distinct but articulated moments. The first, substantiated by the theoretical and documental contribution, which supported the discussions held. The second, consisting of fieldwork, consisting of observations, semi-structured interviews carried out with five women who are mothers, undergraduate students at UFMA, benefited from daycare assistance from the university's student assistance between the years 2018 to 2020 The results revealed that motherhood remains a dilemma for women-mothers who wish to pursue an academic and professional career, given the conditions imposed by the overlapping between patriarchy, racism and capitalism. In this sense, the realization of the right to education, of the National Student Assistance Policy are important advances. However, it is urgent to broaden the debate and strengthen the achievements, which involves struggles to increase funding for the consolidation of a larger project, in defense of democracy, of social policies that guarantee rights such as public education, with quality and with maternity support.